Microneedles for the Noninvasive Structural and Functional Assessment of Dermal Lymphatic Vessels. Issue 8 (4th January 2016) - Brambilla, Davide; Proulx, Steven T.; Marschalkova, Patrizia; Detmar, Michael; Leroux, Jean‐Christophe
Abstract : The medical and scientific communities' interest in the lymphatic system has been growing rapidly in recent years. It has become evident that the lymphatic system is much more than simply a homeostasis controller and that it plays key roles in several pathological conditions. This work describes the identification of the optimal combination of poly(N‐vinylpyrrolidone) and a near‐infrared dye (indocyanine green) for the manufacturing of soluble microneedles and their application to the imaging of the lymphatic system. Upon application to the skin, the microneedle‐bearing indocyanine green is delivered in the dermal layer, where the lymphatic vessels are abundant. The draining lymphatics can then be visualized and the clearance kinetics from the administration site simply determined using a near‐infrared camera. This painless functional "tattooing" procedure can be used for quantitative assessment of the dermal lymphatic function in several dermal conditions and treatment‐response evaluations. The two components of these microneedles are extensively used in routine medical care, potentially leading to rapid clinical translation. Moreover, this procedure may have a significant impact on preclinical lymphatic studies. Abstract : Soluble polymeric microneedles are used to selectively deliver a near‐infrared dye within the dermal layer allowing the identification and visualization of the draining lymphatic vessels. Monitoring the dye clearance kinetics from the application site is used to quantify the lymphatic drainage. This simple and painless "functional tattooing" can be used for the evaluation of the lymphatic function in several dermal conditions.